Wieczność jako pozaludzka czasoprzestrzeń w światopoglądzie ludowym. - Grad, Jan (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
In the magical-religious folk worldview the basic division of time separatedthe temporal time from the eternal time. The first one consists of the cycle of human life where the livelihood of agricultural communities defined by the annual pace of seasonschanges in the nature. The most important dates for a traditional farmer organizationof his work on the farm were marked by holidays and special days devoted toa specific Saint. The eternal time is situated in a completely different dimension. It is theafterlife, “the second world” or “the other world” – a form of the space-time where thespiritual beings exist. From it souls and spirits penetrate into the human world. Theyfulfill specific tasks, voluntarily or recalled by the people who host them during specialmoments of the ritual year.